1997
DOI: 10.1097/00005373-199709000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Noncorrelation between Thoracic Skeletal Injuries and Acute Traumatic Aortic Tear

Abstract: It is generally accepted that the presence of thoracic skeletal injuries has a predictive value for acute traumatic aortic tear (ATAT). The purpose of this study is to objectively assess the validity of that premise. The initial chest radiographs of 548 patients who underwent aortic angiography for suspected ATAT were reviewed for thoracic skeletal injuries. The incidence of thoracic skeletal injuries was compared between patients with and without angiographically confirmed ATAT. Rib fracture is the only thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 12 publications
0
10
1
2
Order By: Relevance
“…Vascular aortic lesions are associated with 3% of the isolated first rib fracture, but this vascular complication rate is 24% when a thoracic, abdominal or cerebral trauma, or a fracture of the long bones exists (9,16). On the other hand, Lee J and colleagues reported that there is no clinically relevant correlation between thoracic skeletal injuries and acute traumatic aortic tears (17). We detected no vascular injuries in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Vascular aortic lesions are associated with 3% of the isolated first rib fracture, but this vascular complication rate is 24% when a thoracic, abdominal or cerebral trauma, or a fracture of the long bones exists (9,16). On the other hand, Lee J and colleagues reported that there is no clinically relevant correlation between thoracic skeletal injuries and acute traumatic aortic tears (17). We detected no vascular injuries in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Mirvis et al [21] found fractures of ribs 1 through 4 in 18% of 41 patients with traumatic aortic injury proved by angiography but with a positive predictive value of only about 21%. Lee et al [22] studied 548 patients who underwent angiography to evaluate for aortic injury and concluded that rib fractures were the only type of thoracic skeletal injury that had a higher incidence in patients with aortic injury (58%) versus those without aortic injury (43%), but the positive predictive value was only 14.8%. This has also been shown at autopsy, where Williams et al [23] retrospectively reviewed 530 motor vehicle fatalities.…”
Section: Discussion Of Procedures By Variant Variant 1: Suspected Ribmentioning
confidence: 99%
“…Dieses Verteilungsmuster zeigt sich auch in der vorliegenden Studie: in 87,8 % resultierte das VT aus einem stumpfen Trauma, davon entfielen 75,0 % auf Verkehrsunfälle. In älteren europäischen Auswertungen stellen sich zwar Pkw-Unfälle als führende Verletzungsmechanismen bei stumpfen thorakalen Aortentraumata (AIS6; VT-2) dar [15][16][17][18], jedoch mit einem weitaus höheren Anteil als in unserer Analyse. Wir fanden einen geringeren Anteil an VT-2 im Rahmen von Pkw-Unfällen.…”
Section: Patienten Und Methodikunclassified